Ladies' Aid: Gentile Noblewomen as Saviors and Benefactors in the Antiquities - Matthews, Shelly (Harvard theological review, 1999)
Three women in Josephus's Antiquities are well known for their purported devotion to Jewish religious practices: Poppaea Sabina, the consort/wife of the emperor Nero, whom Josephus describes as “God-fearing” (θɛοσɛβής); Fulvia, a Roman convert of consular rank whom he pegs as the source of the expulsion of Jews from Rome under Tiberius; and Helena, Queen of Adiabene, also a convert to Judaism. In this article, I show that the stories of these three Gentile noble women, who share an interest in Jewish religious practices, are part of a larger narrative pattern in the Antiquities that repeatedly characterizes Gentile women of high standing as saviors and benefactors of the Jewish people. According to Josephus, imperial women intercede on behalf of Jewish aristocrats before every Julio-Claudian emperor, often with ramifications for the entire Jewish people. He also claims that Domitia, the wife of the emperor Domitian, was one of his own patrons. Patronage on behalf of the Jewish community is integral to the stories of both Fulvia and Queen Helena of Adiabene. Furthermore, the salvific acts of foreign noblewomen feature prominently in Josephus's retelling of the story of Moses early in the Antiquities.